Controllability study on multi-vessel batch distillation column based on level control scheme - Nurul Hazwani, Sabri (2017)
Batch distillation has shown superior advantages over other separation processes for the production of fine and specialty chemicals, pharmaceutical products and seasonal campaign products. Multi-vessel batch distillation column (MVBDC) is an innovation of less-energy efficient batch distillation. MVBDC is a combination of batch rectifier and stripper column. Due to its dynamics behavior and unsteady state process, the control system strategy of MVBDC is necessarily interesting to study. This research discusses in detail the control strategy of MVBDC that is used to separate a non-azeotropic multiple component mixture under total reflux operation. A ternary mixture consisting ethanol, 1-propanol and n-butanol was taken as the case for this study. Maximum fractionating was achieved under total reflux operation. The vessel holdup was kept constant to its optimal value by the level control, in order to maintain the total reflux operation. Sensitivity analysis and controllability study are significant to determine the level of vessel holdup needed to be controlled and to obtain the best controller performance that can ensure the product quality achievable. Hence, the sensitivity analysis that covers the dynamic analysis and is used to determine important variables for the selection of control structure based on open loop behavior is analyzed. Furthermore, the controllability study that covers controller tuning and interaction analysis using Relative Gain Array (RGA) and Singular Value Decomposition (SVD) on MVBDC based on closed loop behavior were also studied. A set of mathematical model equations were developed based on first principles including mass balance and component balance. The model was simulated using MATLAB Simulink. Controller tuning was performed based on Ziegler Nichols (ZN) tuning method and Internal Model Control (IMC). A two-level control was selected as the control structure based on sensitivity analysis. Based on dynamic analysis, proportional (P) and proportional integral (PI) controller were applied to level control and then the performance was compared. Interaction analysis confirmed the best pair of controlled and manipulated variables i.e. reflux flow-level of top vessel holdup and bottom flow-level of middle vessel with condition number equivalent to 1.185. As a conclusion, two level control structure with PI controller and IMC tuning was chosen in order to guarantee the best performance of controller and to ensure the product quality was achieved Apart from ensuring the best performance of the MVBDC control system, less interactive MVBDC control system is also produced.